Principals’ Innovative Leadership Practices and Effective School Supervision in Ikom Education Zone of Cross River State, Nigeria (American International Journal of Nursing Education and Practice, 2020)
The study focused on the relationship between principals’ innovative leadership practices and effective school supervision in Ikom Education Zone of Cross River State, Nigeria. The study adopted correlation research design. The population of the study was 376 respondents. The study adopted census sampling technique, 94 principals, 282 teachers from 94 public secondary schools in the zone were used for the study. A structured questionnaire titled leadership and school supervision questionnaire (LSSQ), was used as the instrument for the study. The instrument was well validated and coefficient obtained ranges from 0.82-0.89 respectively, which indicated reliability for the study. The data analysis techniques adopted for the study were Pearson Product Moment Correlation Coefficient (PPMC) analysis to test hypotheses. The study revealed that principals’ innovative leadership practices such as authentic, cultural, and balanced leadership significantly relates to effective school supervision in terms of instructional delivery, record keeping and maintenance of school facilities in Ikom Educational Zone, Cross River State. The study recommended that principals should ensure that instructional materials, school records, sports and building facilities provided to schools are well kept and utilized for the promotion of teaching and learning effectiveness. Principals should adopt authentic, cultural, and balanced leadership practices in order to enhance effective supervision in the secondary schools on a continuous basis.